Figure of a couple invoking shringara rasa - Temples of India Project Team (Jio Institute, 2024)
Couples invoking shringara rasa (associated with romance, love, and attractiveness between lovers) are framed in panels with pillars and tiered shikhara with gavaksha (horseshoe) motifs. Unlike in other parts of the temple, the faces are not damaged and they wear heavy jewellery, elaborate headgear, and garments, indicating they belong to royalty or a high social class. The central male figure is seated in the lalitasana pose on a raised circular seat. The central female figure is seated on his left thigh, looking towards the man. Both rest their right feet on blooming lotus flowers. The man is embracing the woman, placing his left hand over her left shoulder. The woman reciprocates his gesture by placing her right hand over his right shoulder. The man is caressing the woman’s right breast with his right hand. Chauri dharini (fly whisk bearers) flank the couple.